Scandal on campus. Dietrich Schwanitz reads Niklas Luhmann’s systems theory - Andrzej Denka (Przestrzenie Teorii)
Niklas Luhmann (1927–1998) is one of the most distinguished sociologists of the twentieth cen-tury and the author of systems theory, which to a great extent has been accommodated into lin-guistics. Dietrich Schwanitz (1940–2004), an anglicist, is one of the most interesting interpreters of Luhmann on the basis of literary studies. Schwanitz is also known as a writer and author of the novel Campus (Der Campus, 1995). The main character, a sociologist, Hanno Hackmann, is wrongly accused of the sexual harassment and rape of a student. His reckless romance is exploited by various people in the university milieu to achieve their own goals. In fact, these people are, however, only the representatives of various social systems, especially politics and the media. Striving for re-election, the university rector needs this matter for his campaign, and the media are only interested in a scandalous story to be exploited for some time. Social communication does not reflect reality, and, at the same time, can be described as based on the “reduction of complexi-ty” (“Komplexitätsreduktion”). This is one of the most important concepts in Niklas Luhmann’s work. It turns out that systems theory provides the specific key to interpret the novel.